Analysis The Use of Illocutionary Speech Acts in Learning in Melati Special School Rumbai Pekanbaru - Charlina, Charlina (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This study aims to analyze the use of illocutionary speech acts that special school teachers Melati Rumbai Pekanbaru used in learning process.The problem discussed in this research is the type of speech act of illocutionary used by the teacher in learning.The method used in this researchisdescriptiv equalitative method.Data collecting technique is done through simak technique and recording technique.Data analysis is done through the technique of separating elements determinant (PUP) by classifying or sorting data in accordance with the formulation of the problem that investigated.The data that has been sorted will be analyzed later based on the theory used.The class that used as the object of this research is mixed class for SMPLB level with nine students, seven male and two female students, and SMALB class with six students,five male and one female student.From the result of the research, found that the type of speech act of illocutionary used by special school Melati Rumbai, Pekanbaru teachers in learning are directive, assertive, and expressive.The type of speech act directive generated inthe form of a requesting directive, commands directive, inquiring directive, demanding directive, and banning directive.Types of assertive speech acts in assertive form of complaining assertive, telling assertive, and states assertive, while expressive speech acts are only in the form of praise expressive.